The Effectiveness of CATIN Class on Pregnancy Readiness of Prospective Brides in The Working Area of Citangkil 2 Health Center, Cilegon City - Siti Yuningsih; Marthia Ikhlasiah; Prihayati (Health and Technology Journal (HTechJ), 2024)
Prospective brides and grooms are a strategic target group in efforts to improve their health before pregnancy. Before the wedding, many prospective brides and grooms do not have enough knowledge and information about reproductive health in a family, so that after marriage pregnancies are often not planned well and are not supported by optimal health status. The number of marriages in Indonesia in 2023 will reach 1.58 million and 68,185 will come from Banten Province. Maternal mortality still reaches 127 cases of maternal death per 100,000 births and the incidence of anemia in pregnant women is 9.2% in 2023. The aim of this research is to determine the effectiveness of prospective brides and grooms or CATIN (Calon Pengantin) classes on the pregnancy readiness of prospective brides in the Industrial Area of ​​the Citangkil 2 Community Health Center, Cilegon City. Research methods is qualitative research. Population in this study were prospective brides and grooms who registered at KUA in July 2024 in the Citangkil 2 Health Center Working Area, Cilegon City, totaling 12 informants, consisting of 10 Catins and 2 expert informants from KUA and Health officers. There is an influence of information sources related to the socialization of the catin class program from KUA officers and Community Health Center Health Workers on the pregnancy readiness of the prospective bride and groom and knowing the attitude of the prospective bride and groom, the attitude of the KUA officers and the attitudes of health workers who take part in the catin class. There is a change in attitude after participating in the catin class service.